How Individual Habits Fit/Unfit Social Norms: From the Historical Perspective to a Neurobiological Repositioning of an Unresolved Problem - Lorini, Giuseppe; Marrosu, Francesco (Frontiers in Sociology, 2018)
Human beings are “rule-following animals” or “nomic animals” whose behaviour is strictly supported by social norms that reflect shared expectations on what a particular social context considers as appropriate behaviour. Yet, little is known about the biological processes that determine how we learn to accept a particular social behaviour as the most appropriate, and even less is available to highlight the deepest levels/reasons that motivate the trade-off between the daily practice of individual habits and the processes involved in conforming them to such codified social expectations as norms are. In this essay, the authors set out to investigate this particular human ability which is indeed fundamental to understanding our social world: in doing so we hypothesise that the biologically hardwired structural organization and the phenotype expressed by individual habits are the benchmark where social norms are challenged. However, by suggesting that the manifold modalities of observing or violating the norms can be subtly constrained by the individual neurobiological milieu, one can only add another problem as the essay cannot account for the very essence of this trade-off which remains largely unexplored and open to new exciting questions.